Problematika Motivasi Belajar PAI pada Peserta Didik Muallaf dan Berlatar belakang Keluarga Non Muslim: (Studi Multi Situs di SMAN 16 dan SMAN 17 Kota Surabaya) - Achmad Muhibin Zuhri; Muhammad Zaqqi Ghufron (Indonesian Journal of Islamic Education Studies (IJIES), 2020)
To achieve learning objectives, the enthusiasm of students has an existence that cannot be negotiated, its nature is inherent. This is because the learning process requires awareness and mental readiness that requires a desire or encouragement to learn. In practice, factually, in Islamic religious education, learners from non-Muslim families and converts have its challenges. This reality can be found as is the case in SMAN 16 and SMAN 17 Surabaya city. This study aims to identify the characteristics of learning motivation through the approach of learning psychology. Researchers conduct interviews and in-depth observations in natural setting situations through qualitative research methods with a case study approach. This method aims to describe, analyze phenomena, events, social activities, attitudes, perceptions, and thoughts of individual people. The study found that: First, the problem in the motivation of learning Islamic Education, both mualaf and non-Muslim family students concerning psychic aspects, methods of spending and materials that are too "overdosed" for the size of beginners. Problems like this, can be minimized if the teacher correctly understands the learners' characteristics, plans a mature learning, and uses fun media. Second, the problem of learning motivation in Islamic Education, which includes extrinsic and intrinsic aspects, can be overcome if the teacher acts not only as a conveyor of knowledge but also as a source of inspiration and motivation. Thus, teachers can become trendsetters of science, morality, and inspiration for their students. Increased learning motivation is therefore, not only packaged for â€œhow to knowâ€ but also â€œhow to do and feel.â€